2017
DOI: 10.1016/j.yhbeh.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal oxytocin and a polymorphism in the oxytocin receptor gene are associated with human-directed social behavior in golden retriever dogs

Abstract: The oxytocin system may play an important role in dog domestication from the wolf. Dogs have evolved unique human analogue social skills enabling them to communicate and cooperate efficiently with people. Genomic differences in the region surrounding the oxytocin receptor (OXTR) gene have previously been associated with variation in dogs' communicative skills. Here we have utilized the unsolvable problem paradigm to investigate the effects of oxytocin and OXTR polymorphisms on human-directed contact seeking be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…Subjects of the breed golden retriever were part of a parallel study investigating effects of oxytocin treatment on dogs' human directed social behaviour (Persson et al 2017). Therefore, as part of this parallel study, subsequently to DNA sampling half of the females and half of the males received an intranasal dose of 20 IU oxytocin 45 minutes prior to the behavioural test.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subjects of the breed golden retriever were part of a parallel study investigating effects of oxytocin treatment on dogs' human directed social behaviour (Persson et al 2017). Therefore, as part of this parallel study, subsequently to DNA sampling half of the females and half of the males received an intranasal dose of 20 IU oxytocin 45 minutes prior to the behavioural test.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to SEZ6L, ARVCF and COMT, there are other genes suggested to be associated with dogs' human-directed social behaviour. Previous research has found associations between polymorphisms in the oxytocin receptor gene and social behaviour both during problem solving and in additional situations (Kis et al 2014;Persson et al 2017). The oxytocin receptor gene has also been associated with successful training of detection dogs (Konno et al 2018).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 98%
See 2 more Smart Citations
“…There are also other candidate genes that have been indicated for being involved in dogs' social behaviour, for example hormones and neurotransmitters. Polymorphisms in the oxytocin receptor gene (130,131) and the opioid receptor gene (132) are associated with human-directed social behaviours, and polymorphisms in dopamine and serotonin related genes are associated with human-directed aggression (133).…”
mentioning
confidence: 99%